The Effect of Key Success Factors Based on Business Functions on Competitive Advantage - Anggita Ulfazia Rahmi; Popy Rufaidah (Journal of International Conference Proceedings (JICP), 2018)
The study aims to examine the role of key success factors toward the competitive advantages of Small Medium Enterprises (SMEs) in the Foods and Beverages sectors in West Java. Key Success Factors are variables that significantly affect the competitive position of a company in the industry. The dimension of key success factors is measured through four business functions, namely marketing, HR, finance, and operations. Competitive advantage is a factor that enables organizations to differentiate products or services from competitors to increase market share. The variable of competitive advantage is measured using three dimensions, namely cost leadership, differentiation and focus. The study is executed using quantitative research method through descriptive and verificative methods. The respondents of the study were 133 business owners of SMEs in West Java that manufactured food and beverages. The descriptive analysis was applied to describe the dimensions of the key success factors and the competitive advantage of the SMEs. Whilst the verificative analysis was used to examine the model and the relationship between variables studied. Structural Equation Modeling (SEM) is adopted using LISREL to identify overall relationship between the indicators and the variables as well as the relationship between the variables themselves. The findings of the study show that key success factor has significant effect on competitive advantages. Keywords: Key Success Factor, Competitive Advantage, SMEs, Business Functions, West Java